Solidification and microstructure characterizations of eutectic aluminum-silicon casting alloy with the addition of tinErstarrung und Gefugecharakterisierungen einer eutektischen Aluminium-Silizium-Gusslegierung mit Zinnzugaben - Khatibi, K.; Asmael, M. B. A.; Safaei, B.; Zeeshan, Q. (Wiley-V C H Verlag Gmbh, 2021)
The effects of tin (Sn) addition on aluminum-silicon and alpha-aluminum phase solidification parameters as well as eutectic aluminum-silicon casting alloy microstructure are systematically investigated. In this research, these characteristic parameters are examined by using computer-aided cooling curve thermal analyses. The results of microstructure analyses and cooling curves show that tin alters silicon structure. By increasing the amount of tin up to 1 wt.%, alpha-aluminum phase nucleation temperature, aluminum-silicon phase growth temperature, and last phase solidus temperature increase. The mean area of silicon particles decreases when 0.1 wt.% tin is added but by its further increasing up to 1 wt.%, silicon particle mean area increases. It means that increase of tin content does not lead to silicon structure modification in this type of aluminum-silicon alloy. Besides, by increasing the amount of tin, the reaction temperature of the last phase is increased by the formation of intermetallic compounds such as ternary compounds (Al-Si-Sn).
Keywords: Eutectic; Aluminum silicon alloy; Tin; Solidification; Thermal analysis; Microstructure